Pengaruh Lembap, Termal dan Mekanik Pada Proses Manufaktur Sediaan Tablet - Muhamad Rizqy Maulana; Fitrianti Darusman; Anan Suparman (Bandung Conference Series: Pharmacy, 2023)
Quality of pharmaceutical solid preparations is influenced by the selection of solid phases of both active pharmaceutical ingredients (APIs) and additives, formulation design, and manufacturing processes. The pharmaceutical manufacturing process generally involves humid, thermal and mechanical factors. These three things can cause the transformation of the solid form of a BAF. This will certainly affect the stability and bioavailability of the APIs. In the manufacturing process of felt tablet preparations, there are 3 manufacturing methods, namely wet granulation, dry granulation, and direct felt methods. In this research, a literature study was conducted regarding the influence of moisture, thermal and mechanical on the manufacturing process of felt tablet preparations. The results obtained are that the influence of damp, thermal and mechanical in the manufacturing process of pharmaceutical preparations, especially tablet preparations, can result in a phase transformation of APIs solids which will affect the stability and bioavailability of the drug. Kualitas sediaan padat farmasi dipengaruhi oleh pemilihan bahan aktif farmasi (BAF) maupun bahan tambahan, formulasi, dan proses manufaktur. Proses manufaktur sediaan farmasi umumnya melibatkan faktor lembab, termal dan mekanik. Faktor-faktor tersebut dapat menyebabkan transformasi bentuk padatan suatu BAF yang akan mempengaruhi stabilitas dan bioavailabilitas BAF. Pada proses manufaktur sediaan tablet kempa, terdapat 3 metode pembuatan, yaitu metode granulasi basah, granulasi kering, dan kempa langsung. Pada penelitian ini dilakukan study literatur mengenai pengaruh lembap, termal dan mekanik pada proses manufaktur sediaan tablet kempa. Hasil yang didapat yaitu pengaruh lembap, termal dan mekanik pada proses manufaktur sediaan farmasi terutama sediaan tablet dapat mengakibatkan terjadinya transformasi fasa padatan BAF yang akan mempengaruhi stabilitas dan bioavabilitas obat.